A correlational study of breastfeeding duration among Saudi mothers: The role of self-efficacy, intention, and social support - Nourah. M Al Naseeb; Hanan Badr; Salmah Alghamdi (Belitung Nursing Journal, 2023)
Background: Breastfeeding is an essential source of nutrition for infants and offers numerous benefits for both the mother and child. Despite the consensus on its advantages, limited research in Saudi Arabia has explored the factors influencing breastfeeding duration. Objective: This study aimed to examine the relationships between breastfeeding self-efficacy, intention, social support, and breastfeeding duration. Methods: The study employed a correlational research design, and data were collected from three armed forces hospitals in Taif, Saudi Arabia, from December 2020 to February 2021. The samples comprised 356 conveniently selected breastfeeding mothers, assessed using the Breastfeeding Personal Efficacy Beliefs Inventory, Modified Infant Feeding Intention Scale, and Exclusive Breastfeeding Social Support Scale. Simple linear regressions were conducted for data analysis. Results: Breastfeeding duration was divided into two groups. Group 1 consisted of mothers still breastfeeding at the time of data collection, while Group 2 comprised those who had discontinued breastfeeding. Of the total samples, 51.6% (n = 184) of mothers were classified under Group 1, while the remaining 48.4% (n = 172) were allocated to Group 2. Specifically, 78.3% of mothers had stopped breastfeeding by the time their infants were six months old, and 93.3% intended to introduce formula feeding at three months. In Group 1, the results revealed that self-efficacy (β = 0.625, p <0.001), intention (β = 0.643, p <0.001), and social support (β = 0.612, p <0.001) were positively associated with breastfeeding duration. Similarly, in Group 2, a strong positive correlation was observed between self-efficacy (β = 0.72, p <0.001), intention (β = 0.73, p <0.001), social support (β = 0.699, p <0.001), and breastfeeding duration. These three factors jointly explained 40% of the variance in breastfeeding duration in Group 1 (adjusted R² = 0.4) and 50% in Group 2 (adjusted R² = 0.5). Conclusion: Breastfeeding intention was found to have a more significant impact on breastfeeding duration than self-efficacy and social support. These results can inform nurses and midwives in supporting breastfeeding mothers by providing them with the necessary information and increasing their awareness of breastfeeding-related factors.